Developing a digital learning environment as a condition of digital citizenship - NIKOLAEVA, E.M; KOTLIAR, P.S (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The purpose of the following article is to address the issue of civic education in digital culture. In countries with a small volume of local media education initiatives, analyzing evolving communication culture is essential. This communication culture analysis indicates the need for a new social contract for the university that falls within the scope of consumer logic. The results indicate that effective social interaction, within and outside the university, is possible through the profound influence of new media on educational practices and daily life. RESUMEN El propósito del siguiente artículo es abordar el tema de la educación cívica en la cultura digital. En países con un pequeño volumen de iniciativas locales de educación en medios, es esencial analizar la evolución de la cultura de la comunicación. Este análisis de la cultura de comunicación indica la necesidad de un nuevo contrato social para la universidad que se encuentre dentro del alcance de la lógica del consumidor. Los resultados indican que la interacción social efectiva dentro y fuera de la universidad es posible a través de la profunda influencia de los nuevos medios en las prácticas educativas y la vida cotidiana.